Organizational Health Index and Organizational Agility Maturity Criteria as Measurement Tools of Organizational Transformation Effectiveness - Harjanti, Swasti Sri; Gustomo, Aurik (SBM ITB, 2017)
Abstract. As a response to negative growth in the mobile legacy projection - which supports 50% of Telkom revenue, and a positive high growth projection in the ICT and digital business revenue, Telkom decides to shift the business to digital. To be a successful digital company, Telkom has created strategic initiatives, including organizational transformation adopting Customer Facing Unit (CFU) concept that has been done for several months but there still no evaluation method for the success. This paper purpose is to evaluate the implementation of one human capital management strategic initiatives - CFU transformation implementation success, through Organizational Health Index and Organizational Agility Maturity model and formulate a recommendation for Telkom to create a more healthy and agile organization. This research using 11 synthetized dimension of Organization Health Index and Organizational Agility Maturity Model method as tools. Questionnaire consist of 53 practices that represented by 55 questions that asks about respondents extent to which they agree (satisfaction) and whether it meet respondents expectation. Survey result shows that Telkom already in a healthy condition and agile as an organization. This result concluded that by methods used in this research, the transformation could be stated as a success. However, according to the result, maintain and improvement of current health and agility still needed, especially improvement regarding innovation and learning.Keywords:Organization, organizational agility, organizational health index, telecommunication, transformationAbstrak. Dalam merespon proyeksi pertumbuhan negatif dalam bisnis mobile – yang menjadi 50% sumber pendapatan Telkom, dan pertumbuhan positif yang tinggi di bidang ICT dan bisnis digital, Telkom harus masuk ke dalam bisnis digital. Untuk itu Telkom telah membuat beberapa strategi, termasuk transformasi organisasi yang mengadopsi konsep Customer Facing Unit (CFU). Transformasi ini sudah dilakukan selama beberapa bulan namun belum pernah dievaluasi kesuksesannya. Tujuan dari penelitian adalah untuk mengevaluasi kesuksesan transformasi melalui metode Organizational Health Index dan model Organizational Agility Maturity. Penelitian ini juga merumukan rekomendasi bagi Telkom untuk menciptakan kondisi organisasi yang lebih sehat dan mampu bergerak cepat. Penelitian ini menggunakan sintesa dimensi Organization Health Index dan model Organizational Agility Maturity. 53 indikator dari hasil sintesa diwakili oleh 55 pertanyaan yang menunjukkan kepuasan dan ekspektasi responden. Hasil survey menunjukkan bahwa Telkom memiliki organisasi yang sehat dan mampu bergerak cepat. Kesimpulan dari penelitian ini adalah berdasarkan metode yang digunakan, proses transformasi dapat dikatakan sukses. Namun, usaha-usaha untuk mempertahankan dan meningkatkan kondisi saat ini masih diperlukan, terutama peningkatan terkait inovasi dan pembelajaran.Keywords:Organisasi, organizational agility,organizational health index, telekomunikasi, transformasi